(untitled) (Global Journal of Medical Research, 2023)
An impacted tooth is the one that has lost its ability to erupt fully in the oral cavity If a tooth which is impacted at the age of 18 years has high chances of 30-50 of erupting in the oral cavity by the age of 25 years Studies show that if it does not erupt by the age of 25 years it will not change its position and will remain impacted for the rest of the lifetime There is need of surgical removal of the tooth It requires extensive skills and experience to handle such cases with minimum trauma to the oral tissues With evolution it is seen that there is constant reduction in the jaw size which seems to be the reason for increased chances of impaction Apart from evolution the changes in the dietary pattern with industrial revolution for raw food to its soft texture food which doesn t require much of muscle efforts hinder the proper jaw development leading to increased chances of impaction It is seen that the teeth to erupt first in the oral cavity has rare chances of impaction and vice versa 1